Novel indole-based melatonin analogues substituted with triazole, thiadiazole and carbothioamides: studies on their antioxidant, chemopreventive and cytotoxic activities. (1st November 2016) - Shirinzadeh, Hanif; Ince, Elif; Westwell, Andrew D.; Gurer-Orhan, Hande; Suzen, Sibel
Abstract: Melatonin (MLT) is a well-known free-radical scavenger, involving in the prevention of cellular damage that can lead to cancer, ageing and a variety of neurodegenerative diseases. Research on MLT-related compounds has been required to optimise the maximum pharmaceutical activity with the lowest side effects. In our ongoing research, we have synthesized new indole-based MLT analogues as potential antioxidant agents by modifying the MLT molecule. In this study, we build on previous findings, through the synthesis, characterization and in vitro antioxidant profiling of a series of new indole-based MLT analogues which possess triazole, thiadiazole and carbothioamides on the third position on the indole ring. In vitro antioxidant activity was investigated by evaluating their reducing effect against oxidation of a redox sensitive fluorescent probe and their radical scavenging activity was assessed via the DPPH assay. In addition, in vitro cytotoxic effects of newly synthesized compounds were investigated in CHO-K1 cells using the MTT assay.